Hey! We 've verified this expert answer for you, click below to unlock the details :)
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
A set of equations is given below:
Equation E: a = 5b + 1
Equation F: a = 3b + 4
Which statement describes a step that can be used to find the solution to the set of equations?
Equation F can be written as 5b + 1 = 3b + 4.
Equation F can be written as b + 1 = 3b + 4.
Equation F can be written as a = 3(a − 1) + 4.
Equation F can be written as a = 5(a − 4) + 1.
and the other one is
A student is trying to solve the system of two equations given below:
Equation P: y + z = 6
Equation Q: 8y + 7z = 1
Which of the following is a possible step used in eliminating the y-term?
(y + z = 6) ⋅ −8
(y + z = 6) ⋅ 7
(8y + 7z = 1) ⋅ 7
(8y + 7z = 1) ⋅ 8
Not the answer you are looking for? Search for more explanations.
help i am going to fail!
To approach the first question:
if y = 6x – 3 and y = 3x + 4
I can say that 6x – 3 = 3x + 4. Does that make sense?
If a = Something AND a = Something else
Something = something else
Substitute what a equals in the first equation for a in the second equation, that is your answer
For the second, they want you to use the technique of adding together the two equations to have one variable cancel out.
If you multiply the first equation by (-8), then you will have -8y in the first equation and +8y in the second equation.
Adding the two equations together eliminates the Y variable , (-8y+8y) = 0y